Health Security and Beyond: A Multidisciplinary Review on Safety and Protection - ALJABRI, EMAD HAMOUD; ALJAZAERI, MAMDOH MUSTAFA; ALMUTAIRI, NADA ABDULRAHMAN; ALRUHAILY, AMAL AHMED; ALSAHLI, NORAH ATQAN; ALHARTHI, BATLA SULTAN; ALHARBI, MANAR MUDHHI; ALAQIL, NUHA HUSSAIN A; AL-BARGHI, YARA OMAR (Journal of Posthumanism, 2024)
The restructuring of nursing roles reflects how health security extends beyond direct patient care. Nurses increasingly serve as interpreters of digital health data, bridging patients with technology to ensure safe, informed care (Cummings, Hayduk & Estabrooks, 2022; Faeq, Zyad & Hassan, 2022). Responsibilities now include remote monitoring, interpreting wearable outputs, and coordinating with interdisciplinary teams. These new demands reinforce the role of nurses as essential actors in both individual safety and public health security, ensuring that digital data translates into practical, protective actions within diverse healthcare settings